In vitro α-amylase and α-glucosidase inhibitory activities of selected Malaysian plants and in vivo antidiabetic properties of enema glauca / Mohamad Jemain Mohamad Ridhwan - Mohamad Ridhwan, Mohamad Jemain (2011)
Uncontrolled postprandial hyperglycaemia increases the risk of vascular diabetic complications. One of the therapeutic approaches to control postprandial hyperglycaemia is by inhibiting a-amylase and a-glucosidase enzymes activity. In this study, 50 extracts from 23 Malaysian tropical plants were assayed for a-amylase and a-glucosidase inhibitory activities. A microscale a-amylase inhibition assay was optimized and established based on method previously described by Hasenah et ah (2006). In comparison with the previous method, the microscale assay is simple and consists of less steps, can screen up to 22 samples at a time, decrease consumption of chemicals up to 400 % and produced reliable results. Screening of 23 Malaysian tropical plants using method described by Haseanah et al. (2006) found eight plant species demonstrated potent a-amylase inhibitory activity. The plants were Burkillantus malaccensis (stem), Horsfieldia polyspherula (leaves and stem), Knema glauca (leaves and stem), Labisia pumila (leaves and root) and Phyllantus pulcher (stem). The IC₅₀ values of these extracts ranging from 1.17 to 2.78 µg/mL. Six plant species may be classified as strong a-glucosidase inhibitory activity with IC₅₀ values ranging from 3.4 to 6.1 jag/mL. The plants were Gironniera parvifolia (stem), K polyspherula (leave and stem), K. glauca (leaves and stem), Leea indica (root), P. pulcher (leaves and stem), Rothmannia schoemannii (stem). Extracts of P. pulcher (stem), K. glauca (leaves and stem) and H. polyspherula (leaves and stem) showed potent inhibitory activities against both enzymes. The leaves and stem extracts of K. glauca (Penarahan) belonging to family Myristicaceae were selected and examined further for cytotoxicity and in vivo antidiabetic properties. The leaves and stem extracts exhibited moderate cytotoxicity against normal cell lines of WRL-68 (human liver) with CC₅₀ values of 26.55 and 89.49 µg/mL, respectively. The leaves and stem extracts showed moderate cytotoxicity towards normal cell lines of Vero (African green monkey kidney) with CC₅₀ values of 32.76 and 52.05 µg/ml, respectively. Oral starch tolerance test in normal and diabetic rats showed the leaves extract at all doses (125, 250 and 500 mg/kg) significantly reduced (PO.05) blood glucose level. The similar test showed the stem extract significantly reduced blood glucose level in normal and diabetic rats at dose of 500 mg/kg. Oral sucrose tolerant test showed the leaves extract at dose of 500 mg/kg significantly suppressed (PO.05) blood glucose level in normal rats. Oral glucose tolerance test showed the leaves extract at all doses (125, 250 and 500 mg/kg) significantly suppressed (PO.05) blood glucose level in normal rats. In diabetic rats, the extract at dose of 500 mg/kg reduced blood glucose level significantly. The stem extract demonstrated significant reduction of blood glucose level in normal and diabetic rats at a single dose 500 mg/kg. In a 2-week antidiabetic experiment showed the leaves and stem extracts did not show significant effects on fasting blood glucose level and body weight. This study revealed the potential of K. glauca extracts to control postprandial hyperglycemia in diabetic management.